An Assessment of Effectiveness of Immunotherapy in Pollen Allergic Patients - Zaidi, Nosheen; Javed, Najma; Rehman, Obaidur ur (Annals of Punjab Medical College, 2012)
Background: Allergen-specific immunotherapy (SIT) is a well established treatment option for patients with allergic rhinitis with or without associated asthma that can modify the allergic disease process. Aim: To assess clinical efficacy of immunotherapy in patients presenting with pollen allergy. Study design: A cross sectional hospital based study. Settings and Duration: Conducted at Allergy Center, National Institute of Health (NIH), Islamabad during April – October 2011. Subjects and Methods: 100 patients visiting the Allergy Center, NIH with more than two years history of rhinitis, sneezing, asthma of both genders were included. All patients had positive skin prick test. Selected subjects were explained about the nature of the study and informed consent to participate in the study was taken from them. Information on common clinical presentation, duration of allergy, duration of vaccine use, change in disease attacks after vaccine, and quality of life was recorded on pre developed and pre tested questionnaire. Results: A total of 100 patients were enrolled. 57 patients were found to have allergy against grass, 33 against pollen tree and 53 wereallergic to weed. Common clinical symptoms were sneezing (93%), runny nose (90%) and wheezing (87%) followed by redness in 69% of cases. Majority 66 (65.3%) had positive family history for allergy while 34 (33.7%) did not. Time for which patients were on immunotherapy was 1, 2, and 3 years where majority being on vaccine for one year. Before vaccine only 12 patients used to have less acute and frequent attacks compared to 88 patients who had severe attacks. After starting allergy vaccine 71 patients had complete relief with no acute attacks at all, however 05 patients starting having more frequent acute attacks than before whereas 24 patients reported having less attacks but not complete relief. Quality of life in terms of day to day activities and freedom to move out without having acute symptoms was improved in 82% of cases while 18% of the patients did not have such improvement. Conclusions: Immunotherapy serves to build up long term resistance against the sensitized allergen. Avoidance to allergen, use of medication and immunotherapy are the three regimes employed to combat the disease.